Morphological expressions of antibiotic synergism against Pseudomonas aeruginosa as observed by scanning electron microscopy. - Waisbren, S J (1980)
Antibiotic-induced changes in Pseudomonas aeruginosa were observed by means of a scanning electron microscope. Seven frequent and five less frequent morphological changes were noted. The frequent changes were: (i) elongation; (ii) chain formation; (iii) nub formation; (iv) spheroplasts; (v) surface holes or pits; (vi) super-elongation; and (vii) increased filamentation. The less frequent changes were: (i) rounded ends; (ii) streptococcal forms; (ii) stalked nubs; (iv) surface bulges; and (v) convoluted surfaces. A morphological equivalent of antibiotic synergism was found in which changes were noted due to synergistic combinations of antibiotics that were not observed when the antibiotics were used alone or when a nonsynergistic combination of antibiotics was used.